POTRET BUDAYA GEISHA DALAM NAGASAKI BURA-BURA BUSHI KARYA NAKANISHI REI - Endang Poerbowati (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2017)
Abstract. This article explores the cultural portrait of Geisha in Nagasaki Nova Bura Bura Bushi. The object of this research is the representation geisha in Nagasaki Bura Bura Bushi by Nakanishi Rei published in 2002. This research aims to examine the geisha figure in terms of its culture, which Nakanishi Rei uses to describe Japanese social culture in Japanese society. The research approach applied is qualitative approach. The result of the analysis shows that: first, a geisha must be able to maintain a discussion with guest. Second, a geisha should perform polite language behavior skills. Third, a geisha must follow the prevailing customs. Fourth, in everyday life, geisha has certain behavior patterns. Fifth, geishas figure in Japanese society are regarded to have more abilities as a woman compared with ordinary woman. Keywords: geisha, cultural aspect, polite behavior